Accelerated learning: a study of era Covid-19 experiences to improving student motivation - Asri, Robbi; Suhaili, Neviyarni (Counseling and Humanities Review, 2022)
The pandemic has brought the challenge of maximizing online learning. Students must adjust relevant changes in learning methods during the Covid-19 outbreak that may hinder student motivation. Online learning that is carried out today has caused a lot of decreased learning motivation in students at all levels of education because the learning carried out is only monotonous. As a result, a separate investigation on learning methods is required to be studied. As a result, the author conveys one of the learning methods that can be used to increase motivation during the Covid-19 outbreak, namely the accelerated learning method. This article discusses increasing student learning motivation with accelerated learning methods using relevant literature studies. This article is expected to help teachers in schools in providing references using accelerated learning methods to increase student learning motivation.